Esophageal small‐cell cancer: study of a rare disease. Issue 7 (14th January 2013) - Raja, S.; Rice, T. W.; Rajeswaran, J.; Zhong, J.; Blackstone, E. H.
Summary Optimal treatment of esophageal small‐cell cancer, a rare disease, lacks consensus. Based on its lung small‐cell cancer analog, we hypothesized that chemotherapy with adjuvant radiotherapy would be optimal. This hypothesis was tested by studying the collective published literature. A meta‐analysis of individual patients from 148 articles (1952–2010) explored treatment and outcome of 577 patients with esophageal small‐cell cancer. Hazard function frailty modeling identified optimum therapy after accounting for article‐level and patient‐level heterogeneity. Fifty‐nine percent of publications reported one patient and 25% five or more. Sixty‐six percent of patients were men, mean age was 63 ± 11 years, and 64% had localized disease. One, 3‐, and 5‐year survival was 37%, 14%, and 11%, respectively. Survival variation among articles was substantial (P = 0.004), with survival improving across time (P < 0.0004). Chemotherapy was associated with better survival (hazard ratio [HR] = 0.53, 68% confidence interval [CI] = 0.44–0.65; P = 0.002) than surgery alone, radiotherapy alone, nonstandard therapy, or no therapy. Adding local therapy, either surgery (HR = 0.41, 68% CI = 0.34–0.51; P < 0.0001) or radiotherapy (HR = 0.33, 68% CI = 0.27–0.41; P < 0.0001), to chemotherapy further improved survival. Adding both did not provide further benefit. The strategy of borrowing from consensus treatment of lung small‐cell cancer and analyzing the scarce available esophageal small‐cell cancer literature may be beneficial in the study of rare diseases. It confirmed that chemotherapy should be the mainstay of therapy, with additional benefit from adjuvant therapy with either surgery or radiotherapy; both are not needed.